Dissection and enhancement of prebiotic properties of yeast cell wall oligosaccharides through metabolic engineering. (March 2022) - Kwak, Suryang; Robinson, Scott J.; Lee, Jae Won; Lim, Hayoon; Wallace, Catherine L.; Jin, Yong-Su
Abstract: Saccharomyces boulardii is a yeast clinically used for treating various symptoms of gastrointestinal dysbiosis. Despite their genomic relatedness, S. boulardii has a distinctive cell wall oligosaccharide composition compared to baker's yeast S. cerevisiae, such as higher mannan content. Here we explore the beneficial effects of S. boulardii cell wall oligosaccharides through metabolic engineering. We increased the production of guanosine diphosphate (GDP)-mannose, the substrate for cell wall mannan biosynthesis, by perturbing glycolysis flux and overexpressing the enzymes in the GDP-mannose biosynthesis pathway. Combined with overexpression of a cell wall mannoprotein and dolichol phosphate mannose synthase, the cell wall mannan content of S. boulardii increased up to 52%. The identical engineering resulted in marginal changes in the S. cerevisiae cell wall. S. boulardii showed a higher adhesive capacity against Salmonella enterica Typhimurium than S. cerevisiae, and yeast-bacteria sedimentation rates were positively correlated with cell wall mannan contents. Besides, S. boulardii biomass selectively proliferated Bacteroides thetaiotaomicron over Clostridioides difficile more efficiently than S. cerevisiae, and the selectivity was further enhanced by amplifying the cell wall mannan. Collectively, we report the important prebiotic roles of cell wall oligosaccharides in the protective functions of S. boulardii and present a unique metabolic engineering approach to modulate the functions.